An Impact Assessment of Negative Interest Rates of Central Banks - Jurkšas, Linas (Ekonomika, 2017)
The central bank community has been split into those who started to employ negative interest rates (NIR) and those who do not intend to do so, irrespective of the similarity of the economic situation. Moreover, while five central banks have applied negative policy rates from 2012, the launch time, scope and motives behind differ significantly. The fact that central banks have simultaneously pursued NIR at a time when the global financial system is not in a crisis is unprecedented and is a consequence of several fundamental and mutual factors. So, the purpose of this paper is to find out the motivation behind employing negative policy rates and assess how NIR affect different economic sectors. The statistical analysis reveals that the overall outcome is highly controversial, depending on the weight assigned to each economic sector as well as to short- and long-term goals. On the one hand, NIR lead to an overall positive impact on aggregate consumption, increased well-being of net borrower, investing NFCs, indebted governments and even financial institutions in the short run. On the other hand, savers and banks with high excess reserves and less room to reduce net interest margins are the most negatively affected. The impulse-response functions of created vector autoregression model for the euro area confirms these results: an interest rate reduction shock decreased borrowing and deposit rates, net interest margins but positively affected confidence, bond and equity prices, leading to somewhat higher expectations of economic growth and inflation in the longer term. While the lower bound of NIR remains uncrossed, further rate cuts in the negative territory or keeping them for a prolonged period of time might alter negative externalities. If expectations start looming over the material policy change or materialization of financial systematic vulnerabilities, positive effects of NIR could become more muted in the longer term.
Keywords: negative interest rates; central banks; policy rates; lower bound; financial institutions